2014
DOI: 10.5551/jat.23465
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Small Dense Low-Density Lipoprotein Cholesterol as a Predictor for Future Cardiovascular Events in Patients with Stable Coronary Artery Disease

Abstract: Aim:The aim of the present study was to investigate how small dense low-density lipoprotein cholesterol (sdLDL-C) compared with LDL-C affect the long-term prognosis in patients with stable coronary artery disease (CAD). Methods: sdLDL-C measured by heparin magnesium precipitation and LDL particle size measured by non-denatured gradient-gel electrophoresis were compared in 190 consecutive CAD patients who underwent coronary arteriography between 2003 and 2004 who did or did not develop cardiovascular events dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
62
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(72 citation statements)
references
References 51 publications
8
62
1
1
Order By: Relevance
“…Thus, our observation of relatively strong correlation of non-HDL-C with triglyceride is likely to reflect non only the unsurprising correlation between VLDL-triglycerides and VLDLcholesterol, but also some presence of triglyceride-rich lipoproteins, remnant, and abnormal small particles and low HDL-C concentration, which have been proposed as atherogenic lipoprotein phenotype [31,32]. Of note, the correlation coefficient of non-HDL-C with small dense LDL-C has been shown to be high (r = 0.76) compared to Friedewald-estimated LDL-C (r = 0.60) [19,20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, our observation of relatively strong correlation of non-HDL-C with triglyceride is likely to reflect non only the unsurprising correlation between VLDL-triglycerides and VLDLcholesterol, but also some presence of triglyceride-rich lipoproteins, remnant, and abnormal small particles and low HDL-C concentration, which have been proposed as atherogenic lipoprotein phenotype [31,32]. Of note, the correlation coefficient of non-HDL-C with small dense LDL-C has been shown to be high (r = 0.76) compared to Friedewald-estimated LDL-C (r = 0.60) [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…As occurrence of dyslipidemia is an important feature of MetS, the latter study was considered to highlight the importance of atherogenic dyslipidemia rather than high LDL-C levels [18], while both are features related to, or integrated in, non-HDL-C values. In regard of atherogenic dyslipidemia, small dense LDL-C has been shown to strongly associated with an increased risk of coronary heart disease [19]. Of note, non-HDL-C shows a better correlation with small dense LDL particles than do other lipid parameters including LDL-C [20].…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, we measured the plasma concentrations of total and small dense LDL triglyceride is synthesized in the liver, our results indicate that CEE-induced hepatic stimulation may increase plasma triglyceride. Small dense LDL particles, with a diameter less than 25.5 nm and density ranging from 1.044 to 1.063 g/ml 29) , are known to be associated with an increased incidence of CVD 8,30,31) . Long residence time in the plasma, enhanced oxidizing ability, permeability through the endothelial barrier, arterial proteoglycan binding, and lower affinity for LDL receptors have been proposed as factors for 36) demonstrated that plasma levels of lipid peroxide correlate positively with Cu and the Cu/Zn ratio and negatively with Zn.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, in a recent study of stable IHD patients treated with atorvastatin, plasma concentrations of NT-proBNP, neopterin, lipoprotein(a) [Lp(a)], and soluble receptor for advanced glycation end-products (sRAGE) were predictive of major cardiovascular events, whereas LDL-cholesterol, HDL-cholesterol, triglycerides, hs-CRP, adiponectin, cystatin C, Lp-PLA2, monocyte chemotactic protein-1, matrix metalloproteinase-9, myeloperoxidase, osteopontin, soluble CD-40 ligand, sICAM-1, and soluble vascular cell adhesion molecule 1 (sVCAM-1) were not (55 ). Measurement of other lipid elements believed to be highly atherogenic, including small dense LDL particles may provide prognostic information independently of traditional risk factors concerning cardiovascular events in the secondary prevention setting (56 ), but it is unclear whether they provide prognostic information incremental to high-sensitivity troponins and natriuretic peptides.…”
Section: Metabolic and Renal Biomarkersmentioning
confidence: 99%